Sustainable marketing: A bibliometric study - Lara Félix, Jesús Humberto; Mejía Trejo, Juan (Unidad Editorial UPTC, 2021)
The purpose of this bibliometric study is to investigate the state of the art in the subject of sustainable marketing in the scientific search engines Scopus and Web of Science. A literature search was carried out in the aforementioned search engines. The applied methodology was the bibliometric technique using different refinement criteria to obtain the information, the keywords "sustainability" and "marketing" were used as a search method in the titles, abstracts and keywords. Of the selected documents, it was also refined by areas of interest and the period 2016 to 2021 was considered, resulting in 1,310 documents in Scopus and 1,992 in Web Of Science, giving a total of 3302 the final sum of both amounts. The main findings, the sustainable marketing issue is a frontier issue in the sciences that is growing in the last 6 years, which has been applied in the business and academic world, various business opportunities were detected, in which the innovation, knowledge, emerging markets, business models, market orientation, consumer behavior, stakeholder, and social and corporate responsibility are the area’s most closely related to sustainable marketing. Limitations which study only includes the literature of the aforementioned search engines and the criteria established in the methodology Keywords: Bibliometric analysis, sustainable marketing, strategy. JEL codes: M31